Nonlinear finite element modeling of the impact of brittle rock particles against a flat metallic surface - Araújo, Samuel Gustavo Alves (2021)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.